Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1109/tap.2017.2734159
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale, Local Area, and Transitional Millimeter Wave Propagation for 5G Communications

Abstract: This paper studies radio propagation mechanisms that impact handoffs, air interface design, beam steering, and MIMO for 5G mobile communication systems. Knife edge diffraction (KED) and a creeping wave linear model are shown to predict diffraction loss around typical building objects from 10 to 26 GHz, and human blockage measurements at 73 GHz are shown to fit a double knifeedge diffraction (DKED) model which incorporates antenna gains. Small-scale spatial fading of millimeter wave received signal voltage ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 64 publications
3
122
0
Order By: Relevance
“…More recently, with the increasing interest in mmWave for 5G there have been a growing number of contributions that targeted other frequencies, such as 28 and 73 GHz. The authors of [5] reported a series of measurements performed with a single-input single-output (SISO) channel sounder operating at 73 GHz. Two horn antennas were pointed directly at each other to yield a channel that was dominated by a single LOS component, where a human blocker walked through the link at varying distances between the transmitter (TX) and the receiver (RX).…”
Section: A Blockage Studies Extending Rf Theorymentioning
confidence: 99%
“…More recently, with the increasing interest in mmWave for 5G there have been a growing number of contributions that targeted other frequencies, such as 28 and 73 GHz. The authors of [5] reported a series of measurements performed with a single-input single-output (SISO) channel sounder operating at 73 GHz. Two horn antennas were pointed directly at each other to yield a channel that was dominated by a single LOS component, where a human blocker walked through the link at varying distances between the transmitter (TX) and the receiver (RX).…”
Section: A Blockage Studies Extending Rf Theorymentioning
confidence: 99%
“…A power delay profile (PDP) was recorded at each RX azimuth pointing angle, and the measurements at each location resulted in at most 120 PDPs (some angles did not have a detectable signal above the noise floor). The best RX pointing angle (the direction where the RX got the maximum received power) in the azimuth plane was selected as the starting direction for the RX azimuth sweeps (elevation remained fixed for all RXs), at each RX location measured [18].…”
Section: A Measurement Environment and Proceduresmentioning
confidence: 99%
“…24 directional PDPs (HPBW step increments in the azimuth plane, 360/15 = 24) [18] of one sweep at each location were combined to form one omnidirectional PDP to better illustrate spatial consistency. The denoising was done before this synthesis with a threshold of 20 dB below the peak power of each directional PDP.…”
Section: B Measurement Data Processing and Analysismentioning
confidence: 99%
See 2 more Smart Citations